GROWING STUDENT'S MOTIVATION IN PANCASILA AND CITIZENSHIP EDUCATION WITH THE CONCEPT OF LESSON STUDY - Yono, Cahyono Yono; Mulyana, Dadang Mulyana (International Journal Pedagogy of Social Studies, 2019)
ABSTRACTThis study aims to understand learning with the concept of Lesson Study in growing student motivation. This type of qualitative research with descriptive analysis methods. Class VII, VIII, and IX students in one private junior high school in the city of Bandung as the subject and location of the Research. The data of this research is based on the concept of lesson study that is based on the results of planning, results of implementation, and results of reflection. Then the data is presented and analyzed narratively supported by research results and learning theories as well as lesson study theories and concepts. The learning process with the concept of lesson study can increase the enthusiasm and motivation of student learning when learning Pancasila and citizenship. Learning learning concepts that are launched carefully, and implemented in accordance with planning, can increase student motivation and learning so as to produce better student achievement.Keywords: Learning Motivation, Pancasila Education and Citizenship, Lesson Study